A theoretical study on the line defects in β12-borophene: enhanced direct-current and alternating-current conductances. Issue 8 (8th February 2023) - Liang, Jianxin; Wang, Yue; Yang, Zhi; Xu, Li-Chun; Xue, Lin; Liu, Ruiping; Liu, Xuguang
Abstract : Both the direct-current and alternating-current conductances can be enhanced by the line defects in β12 -borophene, but the mechanisms are different. Abstract : Using density functional theory and the non-equilibrium Green's function method, we theoretically investigated the structures, stabilities, electronic properties, and the direct-current (DC) and alternating-current (AC) transport properties of the line defects in two-dimensional material β12 -borophene. Our results suggest that there exist six line defects that can enhance the stability of β12 -borophene and the line defects have profound influences on the electronic structure of β12 -borophene. Along the zigzag direction, the line defects can change the atomic orbital components of the Dirac cones in perfect β12 -borophene, but the line defects along the armchair direction have complicated influences on the Dirac cones. In the case of DC transport, some of the line defects lead to the constant DC phenomenon and the negative differential resistance effect, and enhance the DC conductances since the line defects exhibit typical one-dimensional characteristics. In the case of AC transport, some of the line defects enhance the AC conductances in the medium-frequency and high-frequency ranges through the photon-assisted tunneling effect. The microscopic mechanisms of the enhanced DC and AC conductances are different. In addition, for a low-frequency range, the equivalent circuits of β12 -borophene and the line defects were also suggested, which will be beneficial for designing borophene-based functional nanodevices.